Study of acromial shapes in relation to gender - Pushpa Nagavalli Basavanna; Roshni Bajpe (Wolters Kluwer Medknow Publications, 2019)
Introduction Subacromial impingement syndrome is considered to be one of the most common musculoskeletal disorders affecting the shoulder j'oint. The obj'ectives of the study were to find out the morphology of acromion process and the presence of enthesophytes in male and female scapulae. Methodology The study was done on 100 male and 100 female adult dry human scapulae of different people, collected from the Department of Anatomy, Kempe- gowda Institute of Medical Sciences, Bangalore. Acromial shapes were classified into 4 types-type I (flat), type II (curved), type III (hooked), and type IV (convex). Acromial spurs (enthesophytes), if any, in the anterior one-third of acromion was noted. Results The most common type of acromion found in both the sexes is type I. Even the enthesophytes were more commonly associated with type I acromion. The study revealed that the acromial shape of dried scapulae did not vary significantly with sex. Conclusion In the present study we could find the four types of acromion mentioned in the literature. Since acromial shapes influence the shoulder pathologies involving acromion, the knowledge on acromial morphology and enthesophytes aid the clinicians during its diagnoses and treatment (acromioplasty). Also, data on morphology of acromion could be used for forensic and anthropological purposes for determining gender, ethnicity, and so forth.